2012
DOI: 10.1002/hep.25787
|View full text |Cite
|
Sign up to set email alerts
|

Sustained telomere length in hepatocytes and cholangiocytes with increasing age in normal liver

Abstract: Telomeres, a validated biomarker of aging, comprise multiple nucleotide repeats capping chromosomes that shorten with each cell cycle until a critical length is achieved, precipitating cell senescence. Only two previous studies focused on the effect of aging in ''normal'' liver tissue, but these studies were compromised by small sample size, limited age range, tissue derived from individuals with an increased risk of senescence, and the use of liver homogenates. We developed a robust large-volume, four-color q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 48 publications
5
42
0
Order By: Relevance
“…However, the mechanisms are not yet completely understood, and in some cases, senescence has been associated with detrimental effects but in others it is not. For instance, telomere dysfunction, a major driver of hepatocyte senescence, has been shown to impair liver regeneration and induce liver cirrhosis in mice36 but was not significantly changed during ageing in the human liver37 and did not predict NAFLD32. Furthermore, chronic inflammation has been reported to drive hepatocyte senescence and contribute to liver fibrosis18 and HCC38.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanisms are not yet completely understood, and in some cases, senescence has been associated with detrimental effects but in others it is not. For instance, telomere dysfunction, a major driver of hepatocyte senescence, has been shown to impair liver regeneration and induce liver cirrhosis in mice36 but was not significantly changed during ageing in the human liver37 and did not predict NAFLD32. Furthermore, chronic inflammation has been reported to drive hepatocyte senescence and contribute to liver fibrosis18 and HCC38.…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of desmin-positive HSCs goes up with aging, the number of α-smooth muscle actin (SMA)-positive HSCs is observed to maintain the same level [24]. Meanwhile, a recent study analyzing the lengths of telomeres in 73 donors has reported that aging-induced decrease in the length of telomeres was limited only to the ones in Kupffer cells and HSCs, and the length of telomeres in cholangiocytes and hepatocytes was not reduced [25]. …”
Section: Aging and Liver Cellsmentioning
confidence: 99%
“…Nuclear area and telomere intensity (a surrogate marker of telomere length) of hepatocytes were assessed using Q-FISH, as previously described in detail [23]. Hepatocytes were identified using unconjugated mouse monoclonal anti-Hepar-1 (Dako, concentration 1:100).…”
Section: Telomere Intensity and Nuclear Areamentioning
confidence: 99%